Unheimliche Schönheiten: Barcelona und Marseille – postindustrielle Hafenstädte in der Kriminalliteratur - Kalt, Daniel (transcript, 2018)
Seedy port cities have turned into metropolises of entertainment by the sea: How has crime literature reacted to that development?